Komunikasi Sampradaya Hare Krsna Di Lingkungan Masyarakat Desa Giri Tembesi Kecamatan Gerung Kabupaten Lombok Barat - Putu Suarbawa; Ni Putu Listiawati; I Wayan Wirata (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2020)
Giri Tembesi Village, Gerung District, West Lombok Regency is one of the villages with a predominantly Hindu population, where stands an ashram of the Hare Krsna Sampradaya followers. During the establishment of the ashram, there is rarely or no conflict with the community around it. Related to this, of course there is a strategy or efforts made by the ashram with the surrounding community in maintaining harmony in the social life of the community in Giri Tembesi Village, Gerung District, West Lombok Regency. Formulation of the problems is: 1) What is the form of communication between the Hare Krsna followers in Giri Tembesi Village, Gerung District, West Lombok Regency? 2) What are the obstacles faced by the Hare Krsna followers in communicating with the community in Giri Tembesi Village, Gerung District, West Lombok Regency? 3) What is the effect of communication between the Hare Krsna devotees to community in social communication in Giri Tembesi Village, Gerung District, West Lombok Regency? The theories used in this research are Structural Functional Theory, Social Construction Theory, and Communicative Action Theory. The research method used in this study is descriptive research using a qualitative approach. Data collection techniques are carried out through observation, interview, and documentation.Based on the results of the research obtained data that can be concluded, namely: 1) The form of communication between the Hare Krsna followers in Giri Tembesi Village, Gerung District, West Lombok Regency is simakrama communication, which is carried out to maintain harmonious relations between the Hindus in Giri Tembesi Village. 2) The obstacles faced by Sampradaya Hare Krsna in communicating with the community in Giri Tembesi Village, Gerung District, West Lombok Regency cannot be carried out simultaniously, this is due to differences in the procedures of religious activities between the Sampradaya Hare Krsna and the community of Giri Tembesi village. To overcome this, the villagers of Giri Tembesi and the Sampradaya of Hare Krsna carried out joint activities such as mutual cooperation on temple vestipal or upakara yajna 3) The impact of the communication of the Hare Krsna devotees with the social communication in Giri Tembesi Village, Gerung district, West Lombok Regency is increasingly close relationship.They feel themselves to be part of the Giri Tembesi community. By attending the invitation held by the people of Giri Tembesi Village as well as those carried out by the Hare Krsna devotees, it proved that the communication that had been carried out run well.